Development of Al2O3 Film on Diatomite for Treating Wastewater Containing Anionic Polyacrylamide - Zhang, Y.; Zhang, C.; Zhang, Y.; Zhang, G.; Liu, Shaomin; Xu, Z. (VCH, 2011)
To efficiently treat anionic polyacrylamide (APAM) with a linear structure in wastewater, an Al2O3 film on the surface of diatomite was prepared via the hydrolysis reaction of AlCl3. The Al2O3-coated diatomite was characterized by FT-IR, XRD, and SEM. The results show that the Al2O3 film can be coated on diatomite. The resulting Al2O3-coated diatomite was utilized to treat wastewater (pH = 7) that contained APAM of 60 mg L–1 and suspended solids of 90 mg L–1. Results show that after wastewater was treated using Al2O3-coated diatomite, the content of APAM and suspended solids in the filtrate can meet the standard for wastewater recycling. Therefore, Al2O3-coated diatomite can be used in treating wastewater containing APAM.